Effectiveness of early detection and coordinated referral of infants before 1 year at risk for autism spectrum and neurodevelopmental disorders in maternal and child protection centre: a French randomised pragmatic trial in a stepped-wedge trial (PRECO-TSA protocol) - Camille Jung; Laurence Caeymaex; Philippe Aegerter; Catherine Delmas; Xavier Xu Wang; Anne-Sylvie Pelloux; Nora Bouaziz (BMJ Open)
Introduction Autism and neurodevelopmental disorders (NDDs) are complex conditions that manifest as significant impairments in social communication and behaviour. Early detection and intervention play a pivotal role in improving outcomes, largely due to the high brain plasticity in infants. The PRECO-TSA study aims to validate the effectiveness of systematic use of the Prévention de l’Autisme (PREAUT) grid for early screening and referral strategies for autism and NDDs in infants, focusing on a coordinated approach that integrates maternal and child protection centre with medical-psychological centres. The goal is to evaluate a streamlined referral system to improve early detection and facilitate effective interventions for children at higher risk of autism.Methods and analysis The PRECO-TSA study is a prospective, pragmatic, multicentre, cluster-randomised controlled trial using an incomplete stepped-wedge design, which maximises external validity. The study includes a 6-month baseline phase, a 3-month semiobservation phase and a 6-month follow-up phase. The 36-month patient inclusion period is followed by a 48-month passive follow-up through the National Health Data System, data collection includes demographic and clinical information, with hierarchical mixed models used to analyse the impact of early screening and referral for autism and NDDs.Ethics and dissemination This study was funded by the French Ministry of Health (PREPS-20-0186) and was approved by Ile de France I Ethics Committee CPP (number CPPIDF1-2023-DI29-Cat2). The results will be submitted for publication in peer-reviewed journals.Trial registration number NCT05815095.